The investigation of the relation between job involvement and organizational commitment - Mohammad Javad Esfahani; Mostafa Emami; Hamid Reza Tajnesaei (Management Science Letters, 2013)
This paper investigates the relationship between job involvement and organizational commitment among lower-level employees in Iranian automaker industry. In this study, job involvement is an independent variable, organizational commitment is dependent variable, and the analysis is performed using 100 randomly selected data through a questionnaire, which consists of four-parts. The study gathers biographical and occupational data using a self-designed 40-item questionnaire. The survey measures job involvement using Kanungo’s 10-item 5-point rating scale and organizational commitment is measured based on Mowday’s 15-item 5-point scale. The study uses different statistical techniques including Pearson Product Moment Correlation Technique and Multiple Regression Analysis. The results indicate that job involvement is strongly associated with organizational commitment. The paper therefore suggests that managers must put in all their efforts to promote job involvement in their companies.